A multimethodic approach for the characterization of manganiceladonite, a new member of the celadonite family from Cerchiara mine, Eastern Liguria, Italy. (1st February 2017) - Lepore, G. O.; Bindi, L.; Di Benedetto, F.; Mugnaioli, E.; Viti, C.; Zanetti, A.; Ciriotti, M. E.; Bonazzi, P.
In the manganesiferous ores associated with the metacherts of the ophiolitic sequences at the Cerchiara mine, Eastern Liguria (Italy), a new Mn-bearing mineral belonging to the mica group has been recently found and characterized. High resolution transmission electron microscopy and electron diffraction tomography studies confirm that the mineral belongs to the mica group. Unit-cell parameters from the powder diffraction pattern are: a = 5.149(1), b = 8.915(1), c = 10.304(1) Å, β = 102.03(1)°, space group C2 or C2/m. On the basis of the electron paramagnetic resonance spectroscopic results, the Mn4+ content represents a very subordinate fraction of the total Mn, the remaining occurring as Mn3+. The Raman spectrum clearly indicates the presence of OH groups in the structure. Laser-ablation inductively-coupled-plasma mass-spectrometry measurements assess the presence of considerable amounts of Li. Assuming all Mn as Mn3+ and 22 negative charges, the empirical formula can be expressed as: (K0.830.17)(Mn3+1.14Mg0.80Li0.20Fe3+0.02)(Si3.89Al0.10)O10[(OH)1.92F0.08] with the sum of the octahedral cations indicating a 'transitional' character between a di- and a tri-octahedral structure. This formula corresponds ideally to the Mn3+ analogue of celadonite, thus expanding the range of solid solution in the celadonite family. The ideal end-member formula KMn3+MgSi4O10(OH)2 can be easily related to celadonite by the homovalent substitution VIMn3+ → VIFe3+. The mineral and its name have been approved by the Commission on New Minerals, Nomenclature and Classification of the International Mineralogical Association, (IMA 2015-052).